Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.6352
|View full text |Cite
|
Sign up to set email alerts
|

Fri0080 survival on Second-Line Biologic Therapy After the Withdrawal of an Anti-TNF Treatment in Patients With Rheumatoid Arthritis: Experience in a Spanish Tertiary Hospital

Abstract: Background:Patients with Rheumatoid Arthritis (RA) have been traditionally treated with other TNF inhibitors (TNFis) after the withdrawal of a first TNFi (cycling). However, due to the increase in the biological therapy options, changing to a biologic agent with different mechanism of action (switching) is an alternative choice. More studies are needed to clarify the role of both strategies in order to guide treatment decisions.Objectives:To analyze the survival of the second biological drug, TNFi or biologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regard to the incidence of COVID-19 in patients with SLE's, data are still controversial, with some reports suggesting comparable incidences (7,(11)(12)(13) and others suggesting higher frequencies than the general population (14)(15)(16). Recently, a meta-analysis showed that the risk of COVID-19 in patients with autoimmune rheumatic diseases was higher compared with control subjects without autoimmune rheumatic diseases (odds ratio: 2.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the incidence of COVID-19 in patients with SLE's, data are still controversial, with some reports suggesting comparable incidences (7,(11)(12)(13) and others suggesting higher frequencies than the general population (14)(15)(16). Recently, a meta-analysis showed that the risk of COVID-19 in patients with autoimmune rheumatic diseases was higher compared with control subjects without autoimmune rheumatic diseases (odds ratio: 2.…”
Section: Introductionmentioning
confidence: 99%